Controversies in the pathological assessment of colorectal cancer - Maguire, Aoife (Baishideng Publishing Group Inc, 2014)
Pathologic assessment of colorectal cancer specimens plays an essential role in patient management, informing prognosis and contributing to therapeutic decision making. The tumor-node-metastasis (TNM) staging system is a key component of the colorectal cancer pathology report and provides important prognostic information. However there is significant variation in outcome of patients within the same tumor stage. Many other histological features such as tumor budding, vascular invasion, perineural invasion, tumor grade and rectal tumor regression grade that may be of prognostic value are not part of TNM staging. Assessment of extramural tumor deposits and peritoneal involvement contributes to TNM staging but there are some difficulties with the definition of both of these features. Controversies in colorectal cancer pathology reporting include the subjective nature of some of the elements assessed, poor reporting rates and reproducibility and the need for standardized examination protocols and reporting. Molecular pathology is becoming increasingly important in prognostication and prediction of response to targeted therapies but accurate morphology still has a key role to play in colorectal cancer pathology reporting.